Slovakia: Safeguarding the Future – Legal and Policy Solutions to Demographic Trends - Garayova, Lilla (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Europe is experiencing a complex set of demographic challenges characterised by declining birth rates, an ageing population, and evolving family structures. These demographic trends have the potential to impact various facets of society, including labour markets, social welfare systems, and intergenerational relationships. To address these challenges, European nations have devised legal solutions, primarily through family policy and family law instruments, aimed at supporting families, parents, and children. Some of these nations have developed strong legal tools in response to this demographic change, while others are struggling. These demographic challenges necessitate comprehensive legal responses that incorporate family policy and family law instruments. By promoting family well-being, supporting parents, and safeguarding the rights of children, these legal mechanisms contribute to addressing the complex demographic issues confronting Europe. Policy-makers must continue to adapt and refine these legal solutions to ensure the sustainability of European societies in the face of demographic change. This country report provides insight into the demographic challenges and their solutions specific to Slovakia.Keywords: protection of families, marriage, matrimony, family law, demographic challenges, family policy